Math, asked by agrim83, 1 year ago

simplify (2.3)²-(0.3)²/(2.3)²-2×2.3×0.3+(0.3)²

Answers

Answered by joelsleeba24
8

let a=2.3 and b=0.3

then the above equation reduces to

\frac{a^{2}-b^{2}  }{a^{2}-2ab+b^{2} } =\frac{(a+b)(a-b)}{(a-b)(a-b)} =\frac{a+b}{a-b}

now substituting 'a' and 'b' we get

\frac{2.6}{2}=1.3

Answered by Divyaalia
6
Hey\: mate, \: here \: is \: your \: answer..
-------------------------------------------------

 = \frac{ {(2.3)}^{2} - {(0.3)}^{2}}{ {(2.3)}^{2} - 2 \times 2.3 \times 0.3 + {(0.3)}^{2} } \\ \\ = \frac{5.29 - 0.09}{5.29 - 1.38 + 0.09} \\ \\ = \frac{5.2}{5.38 - 1.38} \\ \\ = \frac{5.2}{4} \\ \\ = 1.3
-------------------------------------------------

Hope \: it \: helps.....
Similar questions